2016
DOI: 10.1128/jcm.03019-15
|View full text |Cite
|
Sign up to set email alerts
|

Multilaboratory Evaluation of In Vitro Antifungal Susceptibility Testing of Dermatophytes for ME1111

Abstract: h ME1111 is a novel small molecule antifungal agent under development for the topical treatment of onychomycosis. Standardization of the susceptibility testing method for this candidate antifungal is needed. Toward this end, 8 independent laboratories determined the interlaboratory reproducibility of ME1111 susceptibility testing. In addition, we subsequently identified 2 strains as quality control (QC) isolates for the method. In the reproducibility study, 5 blinded clinical strains each of Trichophyton rubru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Finally, we investigated whether to read the MIC values on the 4th or 7th day. We mostly observed enough growth after 4 days, which is in line with other studies 10,20,27 . After 7 days, generally equal or higher MICs were observed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, we investigated whether to read the MIC values on the 4th or 7th day. We mostly observed enough growth after 4 days, which is in line with other studies 10,20,27 . After 7 days, generally equal or higher MICs were observed.…”
Section: Discussionsupporting
confidence: 92%
“…Similar as for the temperature, the inoculum concentration is also a matter of debate (Table 1). While in some studies 18,20,21,27 an inoculum density of 10 3 CFU/mL was used, other studies 22,24‐26,28 showed reproducible results with a concentration of 10 4 CFU/mL. The CLSI reference method for broth dilution antifungal susceptibility testing of filamentous fungi, specifically recommends an inoculum of 1–3 × 10 3 CFU/mL for dermatophytes, while for nondermatophyte moulds 0.4–5 × 10 4 CFU/mL is recommended 9 .…”
Section: Discussionmentioning
confidence: 99%
“…[45] The studies reported that micro broth dilution method requires incubation at 35°C and should be read at the end of 72-96 hour. [484950] Though the incubation period of 3-4 days is generally accepted to read the results, the time duration may exceed for a slow growing dermatophyte. Hence, final reading should be read on the basis of presence of growth in the control well.…”
Section: Antifungal Susceptibility Testing (Afst) Methodsmentioning
confidence: 99%
“…It is highly active in vitro and in vivo against Trichophyton rubrum and Trichophyton mentagrophytes and shows excellent human nail permeability (1)(2)(3)(4). A previous study on its mechanism of action revealed that the molecular target of ME1111 was succinate dehydrogenase (complex II) in the mitochondrial electron transport system (5).…”
mentioning
confidence: 99%